Beach road : a novel - Patterson, James, 1947-; De Jonge, Peter (New York : Warner Vision, 2007)
Montauk lawyer Tom Dunleavy is hired to represent a high-profile triple-murder suspect, local star athlete Dante Halleyville; but the case becomes complicated by his client's popularity and a dangerous secret being protected by members of East Hampton's elite class.
Booklist
Adult.
Adult
Keywords: Attorney and client -- Fiction; Rich people -- Fiction; Trials (Murder) -- Fiction; Attorney and client -- Fiction; Legal stories; Rich -- Fiction; Trials (Homicide) -- Fiction; East Hampton (N.Y.) -- Fiction; East Hampton (N.Y.) -- Fiction; Legal stories